MEASUREMENT OF VISIBILITY BY DIGITAL CAMERA (Perner's Contacts, 2012)
Reduced visibility significantly affects the transmission of Free Space Optical Links and also is a critical factor in traffic safety. Method for measuring visibility using a digital camera is designed and and tested in this paper. The proposed method is able to measure visibility between two fixed given points and uses the definition of visibility of contrast ratio decreased to 2 %. Measured values are successfully validated in presence of two types of fog by comparison with the Kim formula. Further testing of the method revealed that White Balance has to be set properly in relation to the light source.
Keywords: visibility, free space optical link, digital camera, contrast